Twenty Years of Basic Vocational Education Provision in Spain: Changes and Trends - Fernando Marhuenda; Francesca Salvà; Almudena A. Navas Saurin; Miriam Abiétar López (European Research Network Vocational Education and Training (VETNET), 2015)
Our contribution attempts to review basic vocational education programmes in Spain over the past 25 years. We intend to compare the evolution of these programmes in terms of conception and conditions of delivery in order to find out how different they are as skill-formation and remedial systems, as well as  analysing how different political views have an impact upon such provision. We will focus on the current programmes in two regions in Spain where tourism is the main economic strength and source of employment. The authors have been working on several research projects investigating these issues since the late 1990s and we are currently working on two of them.